Theoretical Study of a Pneumatic Device for Precise Application of Mineral Fertilizers by an Agro-Robot - Ihnatiev, Yevhen; Lillerand, Tormi; Liivapuu, Olga; Olt, Jüri; Ігнатьєв, Євген Ігорович (Basel, Switzerland : MDPI, 2025)
EN: This article presents the development of a new pneumatic device for the precise application of mineral fertilizers, designed for use in precision agriculture systems involving farming robots. The proposed device is mounted on an autonomous agricultural platform and utilizes a machine vision system to determine plant coordinates. Its operating principle is based on accumulating a single dose of fertilizer in a chamber and delivering it precisely to the plant’s root zone using a directed airflow. The study includes a theoretical investigation of fertilizer movement inside the applicator tube under the influence of airflow and rotational motion of the tube. A mathematical model has been developed to describe both the relative and translational motion of the fertilizer. The equations, which account for frictional forces, inertia, and air pressure, enable the determination of optimal structural and kinematic parameters of the device depending on operating conditions and the properties of the applied material. The use of numerical methods to solve the developed mathematical model allows for synchronization of the device’s operating time parameters with the movement of the agricultural robot along the crop ows. The obtained results and the developed device improve the accuracy and speed of fertilizer application, minimize fertilizer consumption, and reduce soil impact, making the proposed device a promising solution for precision agriculture.
Keywords: precision agriculture; technological materials; pneumatic transport; farming robot; parameters; pressure; time; точне землеробство; технологічні матеріали; пневматичний транспорт; сільськогосподарський робот; параметри; тиску; Час